An Algorithmic Approach to Perineal Reconstruction. Issue 12 (December 2019) - Westbom, Catherine M.; Talbot, Simon G.
Abstract : Summary: Perineal wounds are one of the more challenging plastic surgical defects to reconstruct. Resections in the perineum vary in size and are frequently complicated by radiation, chemotherapy, and contamination. Furthermore, the awkward location and potential need to maintain function of the anus, urethra, and vagina and to allow comfortable sitting all contribute to the complexity of these reconstructions. In light of this complex nature, many options are available for flap coverage. In this paper, we discuss the properties of perineal defects that make each option appropriate.